2015
DOI: 10.1021/acs.analchem.5b00863
|View full text |Cite
|
Sign up to set email alerts
|

Trans–Cis Isomerization of Lipophilic Dyes Probing Membrane Microviscosity in Biological Membranes and in Live Cells

Abstract: PostprintThis is the accepted version of a paper published in Analytical Chemistry. This paper has been peerreviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the original published paper (version of record):Chmyrov, V., Spielmann, T., Hevekerl, H., Widengren, J. (2015) Trans-Cis isomerization of lipophilic dyes probing membrane microviscosity in biological membranes and in live cells. Corresponding AuthorJerker Widengren: jerker@biomolphysics.kth.se.ABSTRAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…37 The effects of temperature on membranes seen in our experiments are in accordance with previous fluorescence spectroscopy studies, which demonstrated that membrane fluidity is reduced with decreasing temperature. [46][47][48][49][50] Our results confirm the expectation that plasma membrane viscosity of live SH-SY5Y cells responds to temperature and that BODIPY 1 is capable of measuring these changes.…”
Section: Bodipy 1 Reports Temperature Modulations Of the Microviscosisupporting
confidence: 80%
“…37 The effects of temperature on membranes seen in our experiments are in accordance with previous fluorescence spectroscopy studies, which demonstrated that membrane fluidity is reduced with decreasing temperature. [46][47][48][49][50] Our results confirm the expectation that plasma membrane viscosity of live SH-SY5Y cells responds to temperature and that BODIPY 1 is capable of measuring these changes.…”
Section: Bodipy 1 Reports Temperature Modulations Of the Microviscosisupporting
confidence: 80%
“…TRAST measurements were performed on a home-built, epi-illuminated, microscope, the basic configuration and operation principles of which has been described elsewhere 20 . Cytosolic fractions were isolated from cells are described previously 21 , in brief cells were permeabilized using 0.005% digitonin in PBS, incubated on ice for 5min and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…Data analysis: As previously described 20 , the redox kinetics of NADH were determined from so-called TRAST curves, showing how the detected time-averaged NADH fluorescence varied with the excitation pulse-train characteristics (pulse duration)]. In the cellular lysates, 355 nm irradiation resulted in fluorescence from both NADH and flavin compounds in the samples.…”
Section: Methodsmentioning
confidence: 99%
“…While trans-cis (photo)isomerization of various compounds is widely used in molecular photoswitches, over the past decades, most works have been focused mainly on azobenzene derivatives [63], spiropyrans [64], diarylethenes [65], and stilbenes [66], and, until recently, this property of cyanine dyes has not been applied in practice. The use of cyanine photoisomerization in research is mainly for probing microviscosity of microheterogeneous media [67,68]. On the contrary, rigidization of the polymethine chain of dyes is often carried out by introducing "bridges" that suppress internal conversion and photoisomerization processes to increase the stability of the dyes and the fluorescence quantum yield [17,18,69,70].…”
Section: Isomerization Of Cyanine Dyes In Structurally Organized Mediamentioning
confidence: 99%